Association between the severity of histopathological lesions and Mycobacterium avium subspecies paratuberculosis (MAP) molecular diversity in cattle in southern Chile - Verdugo, Cristobal; Marquez, Diego; Paredes, Enrique; Moroni, Manuel; Navarrete-Talloni, María José; Tomckowiack, Camilo; Salgado, Miguel (Frontiers in Veterinary Science, 2023)
The objective was to evaluate the association between the severity of histopathological lesions caused by Mycobacterium avium subspecies paratuberculosis (MAP) infection and the molecular diversity of this pathogen. Blood, ileum, and mesenteric lymph node samples were collected at slaughter, from 1,352 adult cattle [source population 1 (SP1)]. In addition, 42 dairy herds (n = 4,963 cows) were followed for 2 years, and samples from compatible paratuberculosis clinical cases [source population 2 (SP2)] were collected. MAP infection was confirmed using an ELISA test, liquid media culture, and PCR. Isolates were genotyped using five MIRU-VNTR markers. Tissues from confirmed samples were subjected to a histopathological examination. A histopathological severity score (HSS) system was developed and used to grade (0 to 5) the magnitude of lesions caused by MAP. In general, the HSS system assesses the number of foci and degree of macrophage infiltration, together with the presence of multinucleated giant cells (MGCs) and acid-fast bacilli (AFB), in addition to the fusion of the intestinal villi and hyperplasia of the crypts. Despite the large sampling effort, only 79 MAP isolates were successfully genotyped, where 19 different haplotypes were described. A mixed-effect Poisson regression model was used to assess the relationship between haplotypes and HSS values. The model was controlled by animal age, and the farm was used as a random effect. Haplotypes were grouped based on their relative frequency: the most frequent haplotype (group i, 49.4%), the second most frequent haplotype (group ii, 12.7%), and all other haplotypes (group iii, 37.9%). Model outputs indicated that group i had significantly higher HSS values than group iii. In addition, group i was also associated with higher optical density (OD) values of the ELISA test. These results support the existence of differences in pathogenicity between MAP haplotypes. However, results were based on a relatively small sample size; thus, these should be taken with caution. Despite this, study findings suggest that haplotypes would be associated with differences in disease progression, where the dominant haplotype tends to generate more severe lesions, which could be linked to a greater shed of MAP cells than non-dominant haplotypes, increasing their chances of transmission.